2014
DOI: 10.7860/jcdr/2014/7328.4417
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging (MRI) Evaluation of Perianal Fistulae with Surgical Correlation

Abstract: Aims:The purpose of the study was to evaluate the role of Magnetic Resonance Imaging in detection and characterization of perianal fistulae and correlating it with surgical findings.Methods: Fifty consecutive patients with suspected perianal fistulae having one or more external openings were prospectively selected for MRI evaluation. Previously operated or patients with recurrent perianal disease were excluded from the study. MRI findings were recorded according to "St. James's University Hospital MR Imaging C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 13 publications
6
33
0
3
Order By: Relevance
“…The results are in agreement with studies by Siddiqui et al, Singh et al and Becklingham et al who reported sensitivity of 95%, 95.5% and 97%, respectively [1921]. PPV in our study is also comparable to a similar study by Singh et al who reported a PPV value of 97.7% in their study [20]. …”
Section: Disscussionsupporting
confidence: 93%
“…The results are in agreement with studies by Siddiqui et al, Singh et al and Becklingham et al who reported sensitivity of 95%, 95.5% and 97%, respectively [1921]. PPV in our study is also comparable to a similar study by Singh et al who reported a PPV value of 97.7% in their study [20]. …”
Section: Disscussionsupporting
confidence: 93%
“…In a recent study, Singh et al [16] stated that the contrast study can be omitted, particularly while evaluating primary/previously unoperated perianal fistulae because the results of imaging findings on T2-weighted and postcontrast T1-weighted fat saturated sequences were statistically similar. In our study, we focused on the role of STIR sequences in patients with CD in the diagnosis of perianal fistulas and in the evaluation of the extension of the inflammatory process in the perianal and perirectal areas, by comparing STIR and T1-images.…”
Section: Discussionmentioning
confidence: 99%
“…However, contrast medium is still used to assess perianal CD in different radiological centers as demonstrated by many studies [15][16][17]. Recent guidelines reported the usefulness of gadolinium-enhanced T1-weighted sequence for the differentiation between fluid/pus and granulation tissue [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fistül saptanmasında postkontrast yağ baskılı T1 (T1 YB) görüntüler de T2 ağırlıklı görüntüler kadar başarılıdır [22]. Pek çok merkezde olduğu gibi bizim birimimizde de postkontrast T1 YB görüntüler T2 görün-tülerle birlikte alınmaktadır.…”
Section: Mrg Tekniğiunclassified